Day 1 Tue, March 23, 2021 2021
DOI: 10.2523/iptc-21483-ms
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Modelling of CO2 Injectivity Impairment due to Salt Precipitation and Fines Migration During Sequestration

Abstract: Recent studies indicated that reactive interactions between carbon dioxide (CO2), brine, and rock during CO2 sequestration can cause salt precipitation and fines migration. These mechanisms can severely impair the permeability of sandstone which directly affect the injectivity of supercritical CO2 (scCO2). Previous CO2 injectivity change models are ascribed by porosity change due to salt precipitation without considering the alteration contributed by the migration of particles. Therefore, this paper presents t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…120 Salt precipitation is another cause of fines-induced injectivity impairments through making the pores susceptible to fines entrapment by size exclusion capture in thin pore throats. 82,121,122 Mineral dissolution is also likely to increase the portion of dislodged fines in saline aquifers; however, there are some arguments on how it affects the wellbore injectivity. For instance, Pearce et al 113 showed that at lower pH condition of CO 2 -rich brines, the impacts of fines migration can be either negative or positive.…”
Section: Factors Affecting the Injectivity Of Comentioning
confidence: 99%
See 1 more Smart Citation
“…120 Salt precipitation is another cause of fines-induced injectivity impairments through making the pores susceptible to fines entrapment by size exclusion capture in thin pore throats. 82,121,122 Mineral dissolution is also likely to increase the portion of dislodged fines in saline aquifers; however, there are some arguments on how it affects the wellbore injectivity. For instance, Pearce et al 113 showed that at lower pH condition of CO 2 -rich brines, the impacts of fines migration can be either negative or positive.…”
Section: Factors Affecting the Injectivity Of Comentioning
confidence: 99%
“…Salt precipitation is another cause of fines-induced injectivity impairments through making the pores susceptible to fines entrapment by size exclusion capture in thin pore throats. ,, …”
Section: Factors Affecting the Injectivity Of Co2mentioning
confidence: 99%
“…14 These precipitated salts formed can obstruct the flow of CO 2 within the porous rock matrix, thereby impairing the CO 2 injectivity. 15,16 More so, these salt formations can serve as nucleation sites for further precipitation, 10 creating a cycle of injection obstructions and operational disturbances. In extreme cases, the extensive salt buildup can completely block the injection well, rendering the well inoperable and jeopardizing the entire CCS operation.…”
Section: Introductionmentioning
confidence: 99%
“…During CO 2 injection in saline aquifers, the dry scCO 2 stream interacts with the resident brine, leading to the evaporation of water. ,, This evaporation process results in the precipitation of salts, a phenomenon referred to as the drying effect . These precipitated salts formed can obstruct the flow of CO 2 within the porous rock matrix, thereby impairing the CO 2 injectivity. , More so, these salt formations can serve as nucleation sites for further precipitation, creating a cycle of injection obstructions and operational disturbances. In extreme cases, the extensive salt buildup can completely block the injection well, rendering the well inoperable and jeopardizing the entire CCS operation.…”
Section: Introductionmentioning
confidence: 99%